2002
DOI: 10.1086/341776
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Acquired Immunity to aPlasmodium vivaxInvasion Ligand, the Duffy Binding Protein

Abstract: The interaction between the Plasmodium vivax merozoite Duffy binding protein region II (DBPII) and the human erythrocyte Duffy antigen leads to infection. Highly polymorphic regions of this protein may have arisen as a mechanism to avoid host immunity. To examine whether immunity to P. vivax is directed against these polymorphic regions of DBPII, age-associated changes in the frequency of specific DBPII alleles among 358 P. vivax-positive Papua New Guineans were examined. Although the overall number and divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 37 publications
(48 reference statements)
4
95
0
Order By: Relevance
“…These epitopes are predicted to be exposed to the surface of the PvDBP molecule [30]. The putative changes in protein structure may alter antibody binding efficacy of a particular epitope, thereby allowing escape from the host protective immune response [13,30]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These epitopes are predicted to be exposed to the surface of the PvDBP molecule [30]. The putative changes in protein structure may alter antibody binding efficacy of a particular epitope, thereby allowing escape from the host protective immune response [13,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Critical binding motifs in PvDBPII have been mapped to a 170 amino acid stretch (amino acids 291-460), which includes cysteines 5-8 [11,12]. PvDBPII shows the highest genetic diversity compared to the remaining PvDBP regions and appears to be under strong selective pressure [13,14]. Analysis of genetic variation of PvDBPII among P. vivax field isolates from different geographical regions, including Brazil, Colombia, South Korea, Papua New Guinea, Thailand, showed that the PvDBPII is highly polymorphic, but the cysteine residues are conserved within and between P. vivax populations from different geographic regions [14-21].…”
Section: Introductionmentioning
confidence: 99%
“…16,[18][19][20] After natural exposure to P. vivax infection, individuals residing in malaria-endemic areas develop antibodies that block binding of DBP to DARC-positive erythrocytes. 21 It has been hypothesized that polymorphisms in PvDBP-II arose from immune selection 16,[18][19][20][21][22] so that the frequency of nonsynonymous mutations exceeds that of synonymous mutations in PvDBP-II. These polymorphic regions represent B-and/or T-cell epitopes recognized by the host immune response that might inhibit protective immunity against DBP.…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, different studies suggested that stronger humoral and cellular immune responses to PvDBP-II develop progressively with increasing age, 22,24,29,30 showing a boosting effect that was likely because of repeated exposures to the infection. 28 Also, the anti-PvDBP-II antibodies in populations living in areas endemic for P. vivax could block PvDBP-II ligand DARC-positive erythrocytes 21,31 and inhibit erythrocyte invasion in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Region II of DBP (DBPII) may be a critical target for host protective immunity, based on several observations. First, certain regions of DBPII are highly polymorphic (24,25) and appear to be maintained by immune selection (11). Second, antibodies to DBPII from populations in areas endemic for P. vivax inhibit binding of COS-7 cells that express DBPII ligand on their surface to DARC-positive erythrocytes (16,23).…”
mentioning
confidence: 99%